Skal – skal ikke. Jordmødre og psykiatriske sykepleieres erfaringer med varsling av avvik - Ulvund, Ingeborg; Dale, Karl Yngvar; Ødegård, Atle (Nordisk Tidsskrift for Helseforskning, 2015)
Patient Safety has a high priority on the national and international health care agenda. The incidence of adverse events is estimated to be too high and for a variety of reasons, a fair amount of such events are not reported. Hence, the aim of this study was to explore how midwives and mental health nurses experience and deal with adverse events. The study had a qualitative approach. Semi-structured interviews were conducted with 25 midwives and mental health nurses. The data analysis strategy was systematic text condensation. Two primary themes emerged from the interviews: a) Nurses have a moral obligation to report, and b) Adverse events puts the individual in a difficult situation. The findings suggest developing a clearer understanding of the relationship between individual and organizational factors. In addition, management is proposed as the key factor in establishing good practice for reporting. More research is required in order to understand the psychosocial aspects of reporting adverse events, and the dynamics involved in professional decision-making in patient safety activities.